Association between hypodontia of permanent maxillary lateral incisors and other dental anomalies - Santos,Diego Junior da Silva (2020)
ABSTRACT Introduction: Tooth agenesis is often associated with other tooth anomalies, such as microdontia, delayed eruption and ectopic eruption. Moreover, they may be found all in the same individual, as certain genetic mutations may have a variable phenotypic expression. Treatment of cases of hypodontia of anterior teeth should not involve only opening or closing space for prosthetic rehabilitation. Individuals with hypodontia of permanent maxillary lateral incisors may have teeth with a mesiodistal width smaller than that of patients with a normal dentition, and which may need reshaping to achieve an esthetic and functional occlusion. Objective: This clinical case report discusses the association of hypodontia of permanent maxillary lateral incisors with other tooth anomalies and their treatment alternatives.